CO2 nano-foaming of nanostructured PMMA. (10th February 2015) - Forest, C.; Chaumont, P.; Cassagnau, P.; Swoboda, B.; Sonntag, P.
Abstract: PMMA-based nano-cellular materials were produced using a gaseous CO2 foaming process. PMMA has been investigated because of its CO2 -philic behaviour, which allows high CO2 uptake during the foaming process and facilitates the nucleation phenomenon. Nevertheless, one way to further increase the nucleation rate during the foaming process is to create a heterogeneous nucleation inside a polymer/nucleating agents system, while controlling the foaming process parameters. The addition of acrylate-based copolymers as potential nucleating agents to PMMA is the method chosen here to increase the nucleation rate. This study focuses on the foaming of blends of PMMA and acrylate-based copolymers with a batch process using gaseous CO2 and presents the influence of the initial microstructure of the blends on their final foam structures. Under certain conditions, nano-cellular materials with an average cell size lower than 100 nm were obtained, a hundred times lower compared with PMMA foam. Graphical abstract: Highlights: Nano-cellular PMMA/acrylate-based copolymer foams were obtained using a two-stage batch CO2 process. The role of acrylate-based copolymers as a nucleating agent into a PMMA has been shown. The cell growth occurs in a viscoelastic solid during the foaming stage. Nano-cells with an average size lower than 100 nm and with foam densities of about 0.6 g cm −1 were elaborated.